PEMETAAN CAGAR BUDAYA DI DAERAH ISTIMEWA YOGYAKARTA BERBASIS MOBILE - Ermawati -; Erna Kumalasari Nurnawati; Suwanto Raharjo (Jurnal SCRIPT, 2016)
Cultural heritage is the cultural heritage is immaterial in the form of objects of cultural heritage, the heritage buildings, structures of cultural heritage, cultural heritage sites, and the heritage area of land and / or water that needs to be preserved its existence because it has significant value for the history, science, education , religion and / or culture through setting process. Special Region of Yogyakarta (DIY) is famous for its culture and has a lot of cultural heritage. Since the number of cultural heritage in the DIY necessary to the Cultural Heritage Mapping System is beneficial to the community, school children, local tourists and foreign tourists in search for locations and information about cultural heritage in DIY. Materials used in this research is the cultural heritage of data obtained from the Department of Culture DIY. The methodology used is literature study and observation. Heritage Mapping System was built using the programming language PHP, HTML, CSS, MySQL database, Apache web server, text editor Notepad ++ and Android Studio IDE. Heritage Mapping System was built in two different systems, namely the system of web-based and mobile-based system Android. Web-based systems used for processing the data that has three actors, namely admin, manager and operator. This system uses a database that is integrated with other mapping system. While the Android mobile-based system used by the user and assist users in getting the information, the location and route location within cultural heritage in DIY.